Spatiotemporal distribution of thunderstorm initiation in the US Great Plains from 2005 to 2007 - Noah A. Lock; Adam L. Houston (International Journal of Climatology, 2015)
A first‐of‐its‐kind automated thunderstorm tracking algorithm that relies on radar reflectivity data and cloud‐to‐ground lighting is used to identify the spatiotemporal distribution of thunderstorm initiation over the central United States for 2005–2007. Nearly 56 000 thunderstorm initiations are identified. High concentrations of thunderstorm initiation are found near prominent topography and near the Gulf coast. The annual distribution exhibits a peak in August and the diurnal cycle exhibits a peak at the local solar noon with the majority of initiations occurring between 2 h prior to and 6 h past the local solar noon. While the results are largely expected, no previous study has documented the distribution of thunderstorm initiation over the geographic extent and period of record used to develop the results presented here.